Perbandingan Estimasi Anggaran Biaya Antara Harga SNI Dengan Harga Kontraktor Pada Proyek Pembangunan Pagar di Kandangan Surabaya - Akhmad Andi Saputra; Dandy Nugroho; Feri Sukmana (Wahana Teknik, 2020)
The implementation of a construction project is a mechanical series of activities or works that are complex, multi-layered and interdependent. Building construction activities in the field of construction, we need a basic means of calculation of Principal Unit Price Analysis (AHSPK). Contractors are more likely to calculate the price of the work unit based on their own analysis based on previous experience in completing a construction work, although it is inseparable from SNI analysis (Indonesian National Standardization). The research method in analyzing the Budget Plan (RAB), namely the SNI and Contractor Calculation Methods. From the calculation of each analysis of the existing budget plan, the results obtained are a comparison of the budget plan between the SNI method with the Contractor Method. A more economical cost budget plan using the Contractor Method is IDR 548,564,455.00 while the results of the analysis of the SNI cost budget plan is IDR 1,151,860,112.11. Keywords: Budget, Comparison, Contractor, Cost, Estimation, Price, SNI.